The effect of moderate and vigorous aerobic exercise training on the cognitive and walking ability among stroke patients during different periods: A systematic review and meta-analysis - Li, Zecheng; Guo, Hongpeng; Yuan, Yuan; Liu, Xuebin (PloS one, 2024)
The study examined whether rehabilitation using aerobic exercise is more appropriate for patients less than 3 months post-stroke or more appropriate for patients more than 3 months post-stroke. PubMed, Embase, Web of Science, Scopus and CNKI databases were searched from inception to September 2023. All studies included must be written in English and grey literature was excluded. The quality of the study was evaluated using the PEDro scale. Standard mean difference (SMD) and 95% confidence interval (CI) were calculated. The primary outcomes are cognitive ability and walking ability. The intervention of the experimental group must be or include high-intensity aerobic training or moderate-intensity aerobic training. In addition, we required low intensity routine exercises in control group. Only 15 studies were included in this meta-analysis. The results showed that aerobic exercise has a positive rehabilitation effect on cognitive and walking ability of stroke patients. Global Cognitive Function (SMD = 0.81 95%CI 0.49-1.12), Walking Capacity (SMD = 1.19, 95%CI 0.75-1.62), VO2peak (SMD = 0.97, 95%CI 0.66-1.28), and brain-derived neurotrophic factor (SMD = 2.73, 95%CI 2.03-3.43). We further observed that patients who suffered a stroke within the past three months exhibited superior rehabilitation outcomes compared to patients who suffered a stroke more than three months ago, specifically in terms of cognitive ability, walking tests, and cardiopulmonary function. It is recommended to carry out treatment for patients in the initial stage of stroke, and it is required to pay attention to exercise intensity in the process of treatment to ensure patient safety.